2021
DOI: 10.1108/joe-07-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of a social enterprise supporting mothers in Hungary

Abstract: PurposeThe purpose of this paper is to examine how and to what extent social enterprise can contribute to improving women's life in Hungary.Design/methodology/approachThe case study was based on a four-month organizational ethnographic study of a café. Participant and non-participant observations were supplemented with interviews with the founder, the manager, visitors and informal conversations with the staff and visitors. Social media communication was also reviewed.FindingsThe empirical results from the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…Ez ahhoz vezethet, hogy egy társadalmi szempontból értékes cél az egyik fontos kezdő lépést sem éli meg a vállalkozóvá válásban, nem kap pénzügyi támogatást. A kinyilvánított társadalmi célnak összhangban kell lennie a finanszírozó explicit (vagy implicit) elvárásaival, például ha a finanszírozó az integrációt abban látja leghatékonyabbnak, hogy az érintettek dolgoznak, akkor olyan programot fog támogatni, ahol munkaintegrációs program valósul meg (Primecz, 2021;Tóth, 2021). Az izomorfizmus, a környezeti nyomás egy irányba tereli a társadalmi vállalkozókat, mind versenyképesség szempontjából, mind intézményi szempontból (Mason, 2012).…”
Section: Elméleti Alapok: Hibriditás a Társadalmi Vállalkozásoknálunclassified
See 1 more Smart Citation
“…Ez ahhoz vezethet, hogy egy társadalmi szempontból értékes cél az egyik fontos kezdő lépést sem éli meg a vállalkozóvá válásban, nem kap pénzügyi támogatást. A kinyilvánított társadalmi célnak összhangban kell lennie a finanszírozó explicit (vagy implicit) elvárásaival, például ha a finanszírozó az integrációt abban látja leghatékonyabbnak, hogy az érintettek dolgoznak, akkor olyan programot fog támogatni, ahol munkaintegrációs program valósul meg (Primecz, 2021;Tóth, 2021). Az izomorfizmus, a környezeti nyomás egy irányba tereli a társadalmi vállalkozókat, mind versenyképesség szempontjából, mind intézményi szempontból (Mason, 2012).…”
Section: Elméleti Alapok: Hibriditás a Társadalmi Vállalkozásoknálunclassified
“…Bár egyre több empirikus kutatás zajlik az utóbbi időben társadalmi vállalkozások témában Faludi, 2020;Kiss, 2018;Kiss et al, 2020;Krátki-Kiss, 2021;Neulinger et al, 2020aNeulinger et al, , 2020bPrimecz, 2021;Repisky-Tóth, 2019;Takács, 2021aTakács, , 2021bTóth, 2021;, a feltáró interpretatív kutatás tűnt a megfelelőnek, mivel több a nyitott kérdés a magyarországi társadalmi vállalkozások működésével kapcsolatban, mint az ismert eredmények. Ezen belül a narratív interjú technika különösen hasznosnak ígérkezett, mert a társadalmi vállalkozók és a vállalkozásokban dolgozó vezetők spontán a saját megéléseik alapján mutathatták be a vállalkozásukat.…”
Section: Módszertanunclassified
“…Of studies on females' entrepreneurship, the below-mentioned surveys are some examples in Hungary. A recent examination (Primecz, 2021) on the contribution of social enterprise to females' life improvement in Hungary has shown that an award-winning and famous social enterprise in Hungary can only slightly impact the social state of females. In other investigations (Siničáková, 2011; Salamzadeh, Yadolahi Farsi, & Salamzadeh, 2013; Holienka, Jančovičová, & Kovačičová, 2016), the motivators of females' engagement in early-stage entrepreneurial undertakings were studied in Visegrad countries (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The voluntary collection of environmental data by citizens with easy-to-use sensors can be used to eliminate risks such as floods or for scientific or policy-adjustment purposes, such as documenting biodiversity or improving urban quality and livability (DITOs, 2018;Simeone et al, 2021;Wehn and Evers, 2015). Measuring the potential of digital projects for social impact is challenging (Faludi, 2020a, b), and even highly committed projects are less likely to make changes within a restricted sociocultural context (Kiss et al, 2022;Primecz, 2021). How can social impact and applied technology be aligned at a boundedtime events?…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the potential of digital projects for social impact is challenging (Faludi, 2020a, b), and even highly committed projects are less likely to make changes within a restricted sociocultural context (Kiss et al. , 2022; Primecz, 2021). How can social impact and applied technology be aligned at a bounded-time events?…”
Section: Introductionmentioning
confidence: 99%